Ответы и объяснения

Лучший Ответ!
2011-10-09T20:23:56+04:00

x²-4|x+1|+5x+3=0

 

при x∈(-∞,-1>

x²-4(-x-1)+5x+3=0

x²+4x+4+5x+3=0

x²+9x+7=0

Δ=9²-4*1*7

Δ=81-28

Δ=53

√Δ=√53

 

x₁=(-9-√53)/(2*1)

x₁=(-9-√53)/2≈-8,1

 

x₂=(-9+√53)/(2*1)

x₂=(-9+√53)/2≈-0,9 ⇒ не принадлежит (-∞,-1>

 

при x∈(-1,∞)

x²-4(x+1)+5x+3=0

x²-4x-4+5x+3=0

x²+x-1=0

Δ=1²-4*1*(-1)

Δ=1+4

Δ=5

√Δ=√5

 

x₁=(-1-√5)/(2*1)
x₁=(-1-√5)/2≈-1,6 ⇒ не принадлежит (-∞,-1>

 

x₂=(-1+√5)/(2*1)
x₂=(-1+√5)/2≈0,6 

 

x=(-1+√5)/2 ∨ x=(-9-√53)/2